Strategic Learning in Teams - Nicolas Klein (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
This paper analyzes a two-player game of strategic experimentation with three-armed exponential bandits in continuous time. Players face replica bandits, with one arm that is safe in that it generates a known payoff, whereas the likelihood of the risky arms' yielding a positive payoff is initially unknown. It is common knowledge that the types of the two risky arms are perfectly negatively correlated. I show that the efficient policy is incentive-compatible if, and only if, the stakes are high enough. Moreover, learning will be complete in any Markov perfect equilibrium with continuous value functions if, and only if, the stakes exceed a certain threshold.
urn:nbn:de:bvb:19-epub-13221-7
Keywords: C73; D83; O32; 330; Strategic Experimentation; Three-Armed Bandit; Exponential Distribution; Poisson Process; Bayesian Learning; Markov Perfect Equilibrium; Dynamisches Spiel; Arbeitsgruppe; Lernprozess; Trittbrettfahrerverhalten; Gleichgewicht; Test